Online interactive storytelling of product Muhammad S.A.W / Wan Nurul Azreen Nordin - Nordin, Wan Nurul Azreen (2008)
Currently, historical events such as stories of Prophet Muhammad S.A.W are being presented in a linear way like story books. The previous research had proven that storytelling is a better way of learning than linear reading. As the explosion of current technologies, people prefer to have education through easier and attractive medium such as online application. This paper reflects on having an online interactive storytelling of Prophet Muhammad with multimedia elements and branching techniques to produce the interaction. The method used as the research framework is based on the System Development Life Cycle (SDLC), and the implementation of the prototype is based on digital storytelling design structure. As the result of the project, an interactive online storytelling is produced to fulfill the needs of learning about the Prophet's life. Inconclusion, the project can be added with more interaction elements like intelligent agent to allow user-thinking.